2021
DOI: 10.21608/bjas.2021.169126
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Glucose level as Noninvasive Diagnostic Tool for Monitoring Glycemic Control of Type 1 Diabetic Children

Abstract: Current practices for diabetes management rely on monitoring blood glucose levels. The aim of this study was to estimate the glucose levels of saliva, to assess if there is any significant correlation exists between the serum and salivary glucose levels in children with diabetes mellitus type 1. This study was a Prospective case control study included 80 Children aged between 4 and 17 years devidied into case group (60 cases) with Confirmed diagnosis of DM type 1 according to the diagnostic criteria by the Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…DM patients’ blood glucose and parotid salivary glucose levels were substantially higher than those of the control group, and the parotid salivary glucose level was strongly associated with the DM patients’ blood glucose level. This is consistent with previous research [ 44 , 45 ]. Our study showed a significantly strong correlation between UPS and blood glucose levels, whereas there was a significant correlation between whole saliva and blood glucose levels.…”
Section: Discussionsupporting
confidence: 94%
“…DM patients’ blood glucose and parotid salivary glucose levels were substantially higher than those of the control group, and the parotid salivary glucose level was strongly associated with the DM patients’ blood glucose level. This is consistent with previous research [ 44 , 45 ]. Our study showed a significantly strong correlation between UPS and blood glucose levels, whereas there was a significant correlation between whole saliva and blood glucose levels.…”
Section: Discussionsupporting
confidence: 94%